Requirements of protein kinase Cδ for catalytic function: role of glutamic acid 500 and autophosphorylation on serine 643* - Stempka, Luise; Schnölzer, Martina; Marks, Friedrich (The journal of biological chemistry, 1999)
Recently, we reported that, in contrast to protein kinase C (PKC)α and βII, PKCδ does not require phosphorylation of a specific threonine (Thr505) in the activation loop for catalytic competence (Stempka et al. (1997) J. Biol. Chem. 272, 6805-6811). Here, we show that the acidic residue glutamic acid 500 (Glu500) in the activation loop is important for the catalytic function of PKCδ. A Glu500 to valine mutant shows 76 and 73% reduced kinase activity toward autophosphorylation and substrate phosphorylation, respectively. With regard to thermal stability and inhibition by the inhibitors Gö6976 and Gö6983 the mutant does not differ from the wild type, indicating that the general conformation of the molecule is not altered by the site-directed mutagenesis. Thus, Glu500 in the activation loop of PKCδ might take over at least part of the role of the phosphate groups on Thr497and Thr500 of PKCα and βII, respectively. Accordingly, PKCδ exhibits kinase activity and is able to autophosphorylate probably without posttranslational modification. Autophosphorylation of PKCδ in vitro occurs on Ser643, as demonstrated by matrix-assisted laser desorption ionization mass spectrometry of tryptic peptides of autophosphorylated PKCδ wild type and mutants. A peptide containing this site is phosphorylated also in vivo, i.e. in recombinant PKCδ purified from baculovirus-infected insect cells. A Ser643 to alanine mutation indicates that autophosphorylation of Ser643 is not essential for the kinase activity of PKCδ. Probably additional (auto)phosphorylation site(s) exist that have not yet been identified.